Coaching Clinic Model Passing Sepak Bola pada Anak Sekolah Dasar - Ruslan, Ruslan; Podungge, Risna; Mile, Sarjan; Syam, Asry (Jambura Arena Pengabdian, 2024)
Football is a popular sport that has many benefits, both physically, mentally, and socially. One of the basic skills in football is passing, which plays an important role in teamwork and the quality of the game. However, limited facilities, coaches, and structured training programs often hinder elementary school students in Indonesia from developing this skill. This community service activity aims to improve the passing ability of elementary school students through the "Football Passing Coaching Clinic Model" program implemented at SD Negeri 5 Kota Gorontalo. This program involved 30 students in grades 4 to 6 with an interactive approach, including introduction to theory, demonstration of techniques, individual and group training, and small game simulations. The results of the activity showed a significant increase in students' passing ability. As many as 70% of students managed to improve their passing accuracy in pair training with a distance of 5 meters, 50% of students were able to pass with the inside of the foot at a distance of 10 meters with better consistency, and 80% of students showed better ball control skills during small group training. Mini games held at the end of the session also showed improved teamwork and understanding of game strategy. Evaluation shows that this method is effective in training the basics of soccer while increasing students' motivation and self-confidence. This program is expected to be a model for developing soccer skills at the elementary school level, providing positive impacts on both technical abilities and character building of children. With integration into extracurricular activities, this program has the potential to be applied more widely and sustainably.